Efficacy of a Novel Ophthalmic Antimicrobial Drug Combination Toward a Large Panel of Staphylococcus aureus Clinical Ocular Isolates From Around the World. Issue 10 (October 2020) - Laskey, Emily; Chen, Yimin; Sohn, Michael B.; Gruber, Emma; Chojnacki, Michaelle; Wozniak, Rachel A. F.
Abstract : Purpose: Staphylococcus aureus is a leading cause of keratitis requiring urgent antimicrobial treatment. However, rising antibiotic resistance has rendered current ophthalmic antibiotics increasingly ineffective. First, a diverse, ocular S. aureus strain set was evaluated for resistance to 6 commonly used ophthalmic antibiotics. Next, a recently discovered antimicrobial drug combination containing polymyxin B/trimethoprim (PT) + rifampin that displayed impressive efficacy toward S. aureus in both in vitro and in vivo studies was evaluated as a potential novel keratitis therapeutic through testing this combination's efficacy against the clinical strain set. Methods: A total of 163 S. aureus isolates were collected either commercially or from the Flaum Eye Institute, University of Rochester. The minimum inhibitory concentrations of moxifloxacin, levofloxacin, vancomycin, erythromycin, tobramycin, rifampin, and PT were determined for the entire strain set to establish the incidence of resistance to current treatment options among a contemporary clinical isolate set and compared with the performance of PT + rifampin. Results: Among all 163 isolates tested, high rates of antibiotic resistance were found toward erythromycin (69% resistance), moxifloxacin (33%), levofloxacin (40%), and tobramycin (17%). Conversely, the entire strain set, including multidrug resistant isolates, was sensitive to PT + rifampin, demonstrating the potency of this combination. Conclusions: We established that antibiotic resistance is pervasive among clinical S. aureus isolates, underscoring the concern for the effectiveness of current ophthalmic antibiotics. The drug combination of PT + rifampin, however, eradicated 100% of isolates tested, demonstrating the ability to overcome existing circulating resistance factors, and as such, might represent a promising therapeutic for S. aureus keratitis. Abstract : Supplemental Digital Content is Available in the Text.